Pemberdayaan Potensi Lokal melalui Inovasi Kerupuk Jagung untuk Ekonomi Berkelanjutan - K, M. Danil.; Irawan, Feri; Audia, Al; Astria, Niki; Fadhly, Zuhrizal; Sudarman, Sudarman (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
The local potential empowerment program through corn cracker innovation aims to improve the welfare of the community in Kampung Tengah Village, Kuala Batee District, Southwest Aceh Regency. By utilizing the abundant corn harvest, this program teaches production, packaging, and digital marketing skills to the community, especially housewives and MSME players. The methods used include participatory training, technical assistance, and the formation of joint business groups to ensure program sustainability. The program results show an increase in corn cracker production from 20 packs per day to 50 packs per day, as well as an increase in income from IDR 100,000 to IDR 250,000 per day. In addition to the economic impact, the program also strengthens social togetherness through cooperation in a joint business group. Diversification of corn crackers with different flavors and sizes has expanded the market reach outside the district. Constraints faced include product quality consistency and raw material supply chain stability, which can be overcome through collaboration with the government and related institutions. Program sustainability is ensured through the establishment of an integrated marketing network and community capacity building in business management. This corn cracker innovation is expected to become a sustainable model of local economic empowerment and can be replicated in other areas with similar agricultural potential.